Characterization of electrical explosion of Schottky diode for one-shot switch applications. Issue 3 (12th December 2014) - Hu, Bo; Jiao, Jianshe; Zhu, Peng; Wu, Lizhi; Ye, Yinghua; Shen, Ruiqi
Abstract : The electrical explosion characteristics of Schottky diode for one-shot switch applications were acquired by analysis of photographs of high speed camera and current-voltage histories. Four types of connections among Schottky diode, top electrode and discharge capacitor were studied. Results show that type B has the longest time (1.4 ms) of optical radiation and highest energy consumption, which makes it easier to turn on the switch. The charge flux of plasma was determined to be 24.5 Q/(s m 2 ) by parallel electrode plates method. Atomic emission spectroscopic measurements were devoted to determine plasma temperature and density during electrical explosion. Results show that temperature is between 4000 K and 5000 K, and density is about 10 24 m −3 . The one-shot switch based on ceramics has been fabricated and characterized and the results show that the peak current and the rise time are about 963.77 A and 381.6 ns, respectively.